The association of childhood physical abuse, masculinity, intoxication, trait aggression with victimization in nightlife districts. (January 2022) - Miller, Peter; Baldwin, Ryan; Coomber, Kerri; Nixon, Bowman; Taylor, Nicholas; Hayley, Alexa; de Andrade, Dominique
Abstract: Background: High-risk intoxication, trait aggression and conformity to masculine norms are associated with increased risk of barroom aggression; however, less is understood regarding the factors associated with victimization in the night-time environment. Objective: This study aimed to explore the influence of childhood physical abuse, high-risk intoxication, conformity to masculine norms and trait aggression on physical and/or verbal victimization in the night-time environment. Participants and setting: A sample of N  = 490 patrons aged 18–50 years ( M  = 23.02, SD  = 5.89, 58.8% female) were recruited in Fortitude Valley and West End district, Queensland. Method: Participants completed a street interview, including breathalyser, and a follow-up online survey asking about experiences of aggression on the night of interview, experiences of childhood physical abuse and psychosocial correlates. Results: For males, but not females, childhood physical abuse ( OR  = 3.98) increased the risk of physical and/or verbal victimization. Conformity to the masculine norm of Winning ( OR  = 0.21) was protective against physical and/or verbal victimization for males, and trait aggression ( OR  = 1.51) was significantly associated with increased risk of physical and/or verbal victimization for females. Conclusions: These findings add to the growing literature surrounding the long-term impacts of childhood physical abuse, demonstrating experiences of childhood physical abuse are significantly associated with victimization in the night-time economy. The current findings should be taken into consideration when constructing public policy or directed interventions, to help reduce aggression and violence in the night-time economy.